Trends in child poverty in Sweden: parental and child reports - Mood, C; Jonsson, J (Springer, 2016)
We use several family-based indicators of household poverty as well as child-reported economic resources and problems to unravel child poverty trends in Sweden. Our results show that absolute (bread-line) household income poverty, as well as economic deprivation, increased with the recession 1991–96, then reduced and has remained largely unchanged since 2006. Relative income poverty has however increased since the mid-1990s. When we measure child poverty by young people’s own reports, we find few trends between 2000 and 2011. The material conditions appear to have improved and relative poverty has changed very little if at all, contrasting the development of household relative poverty. This contradictory pattern may be a consequence of poor parents distributing relatively more of the household income to their children in times of economic duress, but future studies should scrutinze potentially delayed negative consequences as poor children are lagging behind their nonpoor peers. Our methodological conclusion is that although parental and child reports are partly substitutable, they are also complementary, and the simultaneous reporting of different measures is crucial to get a full understanding of trends in child poverty.